Successful Team Strategy in Winning Regional Head Candidate Pairs (A Study of the Sambas District Elections from 2011, 2015 and 2020) - Asmadi; Elyta; Padilah, Ahirul Habib; Afhiani, Syarifah Nurma (International Journal of Sustainable Applied Sciences, 2024)
Successful team strategies in political campaigns involve various tactics and strategies designed to win voters' votes. Data Collection: Data collection through surveys and polls can help successful teams understand current issues that are important to voters and develop relevant campaign messages. Online Campaigns: Online campaigns have become more popular in modern political campaigns and can help successful teams build voter engagement and expand a campaign's reach. Live Campaigns: Live campaigns such as campaign tours, rallies, and candidate debates remain an important part of political campaigns and can help successful teams build relationships with voters and amplify campaign messages. Social Media: Social media can be a highly effective tool in modern political campaigns and can help successful teams build voter engagement, expand campaign reach, and amplify campaign messages. Positive Campaigns: Campaigns focusing on positive messages and a strong vision can help successful teams build strong support from voters. Assembling a Strong Team: A successful team of experienced people with different skills can help strengthen the campaign and ensure that the right strategies are used to win the election. Financial Management: Effective financial management can help successful teams maximize the use of resources and ensure that campaigns run smoothly.